The Android-Based Cashier Service Information System Utilizes the Waterfall Method - Hafidz, Khairul; Ikhwan, Ali (Asosiasi Doktor Sistem Informasi Indonesia, 2024)
The advancement of information technology aimed to enhance efficiency in information management, including rapid and timely processing as well as accuracy of information. Resto Sampali (Sp) Kitchen frequently encountered challenges in manually recapitulating data due to the necessity of recording sales and purchases individually each day, stored in logbooks. This situation led to inefficient transaction management, resulting in a lack of information regarding product sales, customers, peak hours, and other crucial data essential for strategic decision-making. Furthermore, incomplete transaction records caused uncertainty in tracking income and expenditure flows, thereby increasing the risk of human error and fraud. Manual recording methods also jeopardized data integrity and validity. This research aimed to address these issues by constructing an Order and Payment Management Information System integrated within an Android-based Cashier Service, utilizing a qualitative approach and the waterfall system development method. Results from system testing via Blackbox Testing indicated that the system operated in accordance with the anticipated design, enhancing accuracy in transaction management, revenue, and payments, while delivering a more satisfying experience for customers and café owners.